Programming China: the Communist Party’s autonomic approach to managing state security - Hoffman, Samantha R. (2017)
Programming China: The Communist Party’s Autonomic Approach to Managing State Security, introduces the new analytical framework called China's “Autonomic Nervous System” (ANS). The ANS framework applies complex systems management theory to explain the process the Chinese Communist Party calls “social management”. Through the social management process, the Party-state leadership interacts with both the Party masses and non-Party masses. The process involves shaping, managing and responding and is aimed at ensuring the People’s Republic of China’s systemic stability and legitimacy—i.e. (Party-) state security. Using the ANS framework, this thesis brings cohesion to a complex set of concepts such as “holistic” state security, grid management, social credit and national defence mobilisation. Research carried out for the thesis included integrated archival research and the author’s database of nearly 10,000 social unrest events. Through ANS, the author demonstrates that in the case of the People’s Republic of China we may be witnessing a sideways development, where authoritarianism is stabilised, largely through a way of thinking that both embodies and applies complex systems management and attempts to “automate” that process through technology designed based on the same concepts. The party's rule of China, thus, evolves away from traditional political scales like reform versus retrenchment or hard versus soft authoritarianism. The ANS framework should be seen not as an incremental improvement to current research of China’s political system but as a fundamentally different approach to researching and analysing the nature of Chinese politics.